2014
DOI: 10.1097/rli.0000000000000015
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh-Resolution Imaging of the Human Brain with Phase-Cycled Balanced Steady-State Free Precession at 7 T

Abstract: Objective To acquire ultra-high resolution images of the brain using balanced steady-state free precession (bSSFP) at 7.0T and to identify the potential utility of this sequence. Materials and Methods 8 subjects participated in this study after providing informed consent. Each subject was scanned with 8 phase-cycles of bSSFP at 0.4mm isotropic resolution using 0.5 NEX and two-dimensional parallel acceleration of 1.75 × 1.75. Each phase cycle required 5 minutes of scanning, with pauses between the phase cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…MR imaging at 7.0 T recently has been introduced Implication for Patient Care n MR imaging at 7.0 T may provide a powerful tool with which to noninvasively visualize the depth of mural invasion by gastric carcinomas. as a means of acquiring high-spatialresolution MR images of the brain and intracranial diseases (19,20). To our knowledge, however, there have been no reports of using high-spatial-resolution 7.0-T MR imaging to evaluate the depth of mural invasion by gastric carcinomas.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…MR imaging at 7.0 T recently has been introduced Implication for Patient Care n MR imaging at 7.0 T may provide a powerful tool with which to noninvasively visualize the depth of mural invasion by gastric carcinomas. as a means of acquiring high-spatialresolution MR images of the brain and intracranial diseases (19,20). To our knowledge, however, there have been no reports of using high-spatial-resolution 7.0-T MR imaging to evaluate the depth of mural invasion by gastric carcinomas.…”
Section: Discussionmentioning
confidence: 96%
“…MR imaging at 7.0 T yields the highest field strength that is currently available in clinical MR systems (19,20). Since the signal-to-noise ratio increases almost linearly with field strength, 7.0-T MR imaging systems offer the flexibility to use a higher intrinsic signal-tonoise ratio than standard-field-strength systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying the hippocampus at high-resolution in-vivo may lead to better imaging biomarkers and improve diagnostic accuracy (Kerchner, 2011; Kerchner et al, 2010; Yushkevich et al, 2009). We have recently shown that at 7.0 T, balanced steady state free precession (bSSFP) demonstrates high signal-to-noise ratio and produces a superior depiction of the MTL (Zeineh et al, 2014). In this study we have used the bSSFP sequence at 7.0 T to further investigate the ultra-structure of the hippocampus, and have found that we can reliably identify the EF pathway in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…3). [37][38][39][40] As with other specific techniques such as susceptibility weighted imaging, 39 time of flight magnetic resonance angiography at ultrahigh field should be markedly superior to that at 3 T. Advances in TOF imaging technique are ongoing, with amelioration of SAR constraints enabling venous suppression, 41 improving excitation fidelity, leading to higher contrast, and achieving smooth slab transitions. 42 Carotid imaging at 7 T has attracted substantial attention, given the importance of spatial resolution in evaluating the carotid wall and atherosclerotic disease.…”
mentioning
confidence: 99%